POTENSI PENGEMBANGAN ALFALFA (Medicago sativa L)SEBAGAI BAHAN PANGAN DAN PAKAN TERNAK - Renan Subantoro; Lutfi Aris Sasongko (Universitas Wahid Hasyim, 2017)
Crops alfalfa (Medicago sativa L) is often called a lucerne or medic purple longday plant species, so the flowering process is strongly influenced by the long irradiation . In order to produce flowers and seeds need extra illumination at night , in order to obtain a higher exposure than the critical point . Alfalfa crops in Indonesia was not easy to produce flowers and seeds are formed . At this time there has been no research on the effects of long exposure to the optimum alfalfa seed production, both in quantity and quality. Materials used in this study are three varieties of seed alfalfa (Medicago sativa L) covers multiking1 , vernal and common. The research using a completely randomized design with three replications. Research a factorial experiment with the treatment of various kinds of varieties of alfalfa and Rhizobium with three replications .in conclusion, alfalfa is a sub- tropical crops that can grow and produce flowers and seeds in Indonesia . With the addition of long- day treatment that alfalfa is capable of producing flowers and seeds . The length of the treatment is also supported by the location of the crops that are grown in the lowlands so that the temperature is relatively supportive for flowering and seed formation . Alfalfa crops were grown in Indonesia also have a good enough quality nutrients that can be utilized as raw material for medicine and fodder .Key Word : alfalfa, long day plant, long day, flower, seed